Etika Dalam Masyarakat Madani (Perspektif Dakwah Islam) - Misrah Misrah (An Nadwah, 2019)
One of the values consisting in public model madani is ethics. Ethics is universal element in developing public madani, because ethics relate to attitude, habit, order, actions and morale having the character of correctness about goodness and badness.